Transport losses in market weight pigs: II. U.S. incidence and economic impact - Ritter, Matthew J; Yoder, Chad L; Jones, Corey L; Carr, Scott N; Calvo-Lorenzo, Michelle S (Translational animal science, 2020)
An industry survey representing approximately 310 million (M) market weight pigs was conducted with 20 U.S. slaughter facilities over the calendars years of 2012 to 2015 to determine the incidence, seasonal patterns, and estimated economic impact of dead and non-ambulatory pigs. Each plant entered daily totals in a secure online database for the following variables: 1) pigs slaughtered, 2) dead on arrival (DOA; dead on the truck), 3) euthanized on arrival (EOA; non-ambulatory pig with an injury that required euthanasia), 4) dead in pen (DIP; died after unloading), and 5) non-ambulatory (pig unable to move or keep up with the rest of the group from unloading to stunning). Total dead pigs were calculated as DOA + EOA + DIP, and total losses were calculated as non-ambulatory + total dead. The economic impact was estimated based on the 4-yr weighted averages from USDA annual reports for market swine slaughtered (108,470,550 pigs), live market weight (126.9 kg), and live market price ($1.44/kg). The 4-yr weighted averages for total dead, non-ambulatory, and total losses were 0.26%, 0.63%, and 0.88%, respectively. Total dead consisted of 0.15% DOA, 0.05% EOA, and 0.05% DIP. The months with the highest rates of total dead were July (0.29%), August (0.32%), and September (0.30%), while the lowest incidence rates occurred in February (0.22%), March (0.22%), and April (0.22%). The months with the highest rates of non-ambulatory pigs were observed during the months of October (0.70%), November (0.71%), and December (0.70%), whereas the lowest rates of non-ambulatory pigs were observed during the months of April (0.57%), May (0.53%), and June (0.54%). The following assumptions were used in the economic analysis: 1) dead pigs received no value and 2) non-ambulatory pigs were discounted 30%. Based on these assumptions, the annual cost to the industry for dead and non-ambulatory pigs was estimated to be $52 M ($0.48 per pig marketed) and $37 M ($0.35 per pig marketed), respectively. Therefore, total losses represent approximately $89 M in economic losses or $0.83 per pig marketed. This is the first industry-wide survey on the incidence of transport losses in market weight pigs at U.S. slaughter facilities, and this information is important for establishing an industry baseline and benchmark for transport losses that can be used for measuring industry improvements.